Comparison of Autologous Platelet-Rich Plasma (PRP)-Soaked Dressing vs. Saline-Soaked Dressing in the Healing of Diabetic Foot Ulcer - Gulzar, Hafiz Saad; Iqbal, Muhammad Arslan; Gulzar, Muhammad Hamza; Abbasi, Muhammad Usman (Biological and Clinical Sciences Research Journal, 2025)
Diabetic foot ulcer (DFU) remains one of the most debilitating complications of diabetes mellitus, contributing significantly to morbidity, disability, and healthcare costs. Impaired wound healing due to neuropathy, ischemia, and infection is a major clinical challenge. Platelet-rich plasma (PRP), an autologous source of concentrated growth factors, has emerged as a promising biological therapy to enhance wound repair and tissue regeneration. This study aimed to compare the efficacy of PRP-soaked dressings versus conventional saline-soaked dressings in promoting healing among patients with diabetic foot ulcers in a Pakistani population. Methods: This randomized controlled trial was conducted in the Department of Surgery, Bahawal Victoria Hospital, Bahawalpur, Pakistan, from January 2024 to July 2024. A total of 150 patients with Wagner Grade I or II DFUs were enrolled through non-probability consecutive sampling and randomly allocated into two equal groups. Group A received autologous PRP-soaked dressings, while Group B received saline-soaked dressings. Primary outcome measures included complete ulcer healing within six weeks and reduction in ulcer area; secondary outcomes were mean healing time and proportion of non-healing ulcers. Data were analyzed using SPSS 25.0, and a p-value < 0.05 was considered statistically significant. Results: The mean age of participants was 54.6 ± 8.9 years, with males comprising 64.7% of the sample. Baseline ulcer areas were comparable between the PRP (5.6 ± 2.2 cm²) and saline groups (5.4 ± 2.5 cm²; p = 0.68). After six weeks, the mean ulcer area reduced to 0.9 ± 0.7 cm² in the PRP group versus 2.7 ± 1.2 cm² in the saline group (p < 0.001). Complete healing was achieved in 86.7% of PRP-treated patients compared to 64.0% in the saline group (p = 0.002). The mean healing time was significantly shorter with PRP (28.3 ± 6.2 days) than with saline (35.9 ± 7.1 days; p < 0.001). Stratified analysis revealed consistent benefits across age, gender, and smoking subgroups, with the most significant effects in non-smokers (p = 0.003). Conclusion: Autologous PRP-soaked dressings markedly enhance healing outcomes in diabetic foot ulcers compared with saline-soaked dressings, offering a faster rate of epithelialization and higher complete-healing rates. PRP represents a cost-effective, biologically active adjunct that can be integrated into standard wound-care protocols to reduce morbidity associated with DFUs in resource-limited healthcare settings such as Pakistan.